Proceedings of the 2015 2nd International Conference on Machinery, Materials Engineering, Chemical Engineering and Biotechnolog 2016
DOI: 10.2991/mmeceb-15.2016.91
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Ozone and NOx Production under AC Corona Discharge in Dry Air Used for Faults Diagnostic

Abstract: Abstract. Air is one of the most widely used insulation medium in power systems. However, up to now there is no any existing quantitative gas analysis method used for fault diagnostic based on air by-products detection and analysis. In this paper, a new discharge diagnostic method -gas analysis method based on air by-products (ozone and NO x ) is proposed. The feasibility of this method is studied in this paper. Firstly, the chemical reaction of air under discharge is analyzed; then a typical partial discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…At 420 • C, the NO 2 /NO ratio was decreased to 0.25 and NO was produced with an energy consumption of 24-67 MJ/mol. An opposite tendency was claimed by Li et al [94], who observed that the NO 2 /NO ratio slight increased from 0.67 at 273 K to 0.80 at 373 K in their study using a corona discharge. It should be noted that the gas temperature varies largely for different types of plasma, reactors and operation parameters, so the temperature effect should be considered along with other factors but not separately.…”
Section: Operation Parametersmentioning
confidence: 55%
“…At 420 • C, the NO 2 /NO ratio was decreased to 0.25 and NO was produced with an energy consumption of 24-67 MJ/mol. An opposite tendency was claimed by Li et al [94], who observed that the NO 2 /NO ratio slight increased from 0.67 at 273 K to 0.80 at 373 K in their study using a corona discharge. It should be noted that the gas temperature varies largely for different types of plasma, reactors and operation parameters, so the temperature effect should be considered along with other factors but not separately.…”
Section: Operation Parametersmentioning
confidence: 55%
“…NO was 24-67 MJ/mol. Li et al [111] noticed an opposite trend, with the NO2/NO ratio slightly increasing from 0.67 at 273 K to 0.80 at 373 K in their corona discharge investigation. It should be emphasized that the gas temperature changes greatly depending on the type of plasma, reactor, and operation parameters used; therefore, the temperature effect should be evaluated alongside other aspects rather than independently.…”
Section: Plasma N 2 Fixationmentioning
confidence: 88%
“…Nevertheless, to the best of our knowledge, only a few works have paid attention to the importance of gas temperature on nitrogen fixation in NTP [32], despite the capability of gas heating for shifting and controlling the reactions in NTP and for increasing the vibrational excitation of N 2 . Gas heating in plasma reactors affects the plasma characteristics (especially the electron distribution function) from a different point of view; for example, it may cause a decrease of nonequilibrium degree in the discharge, which could lead to a drop in the generation efficiency of the desired reactive species [33][34][35]. Gas temperature also significantly affects the chemical reactions in the plasma processes.…”
Section: Introductionmentioning
confidence: 99%
“…Malik et al [33] studied the effect of temperature in the range of 20 °C-420 °C on the production of NO x in surface discharge and found that NO was dominant at higher temperatures. Li et al [35] calculated the NO x production under AC corona discharge and found that the ratio NO/NO 2 decreased when the temperature increased from 273 to 313 K. Tang et al [31] also found that the temperature associated with the increase in energy density plays a vital role in the selectivity of nitrogen-oxide products. Although these works studied the effects of temperature on the yield and behavior of products, such an effect of the temper ature on the total amount of fixed nitrogen is not clear.…”
Section: Introductionmentioning
confidence: 99%